The teaching of social studies in selected elementary schools of Quezon City and their implications for Kathmandu, the capital city of Nepal - Gupta, Om Prakash 1935- ([Quezon City s.n.], 1965)
This is an investigation of the lessons that are being taught in social studies in elementary schools in Quezon City, the methods and techniques that are used, the teaching aids and resource materials that are commonly used, the evaluation of social studies teachers by their pupils, and the implications of the findings of this study for Kathmandu (Nepal).
Thesis (M.Ed.)--University of the Philippines
Keywords: Social sciences -- Study and teaching (Elementary)